Magnetic field-induced thermal behavior and sedimentation of strontium ferrite-PDMS composites for actuator applications - Md Anisul Islam; Md Nayeem Hasan Kashem; Wei Li; Wilhelmus J. Geerts (AIP Advances)
Magnetic composite polymers combine the properties of both magnet and polymers which enable them to produce complex shape magnetic components. These materials have potential applications ranging microfluidics, vibration dampers, actuators, and minimally invasive medical devices, because when magnetic fields are applied to them, they can change shape precisely, quickly, and consistently. Our study investigates the behavior of strontium ferrite particles [SrO(Fe2O3)6] suspended in polydimethylsiloxane (PDMS) under the influence of gravity, applied magnetic fields, and time dependent behavior at different temperatures. We found that curing the PDMS and strontium ferrite suspension without a magnetic field result in a well-distributed particle arrangement with no coagulation. However, the particles align along the magnetic field lines while curing in the presence of a magnetic field (Hallback Cylinder), leaving a clear PDMS layer on top, while there is very little sedimentation due to gravity. To check this, we fabricated a 40 mm long sample and conducted hysteresis measurements in vibrating sample magnetometer (VSM) at various positions, showing minimal variation in magnetic saturation (Ms) values. Furthermore, we found a time-dependent curve of the transient angle as a function of temperature change, where the angle decreased over time as the particle’s magnetic moments aligned with the direction of the magnetic field. At lower temperatures, the transient angle decreased sharply due to lower dynamic viscosity in the uncured specimen. Hysteresis analysis and time-dependent studies at varying temperatures showed a notable change in curing that occurs at ∼55 °C, indicating the transition from a magneto-rheological fluid to a magnetorheological elastomer. The packing fraction of strontium ferrite particles and saturation magnetization were correlated, while coercivity was field-angle independent and remanence was field angle dependent.